Pacific oral health: a scoping review - Hanif, Naailah Zahraa; Morse, Zac; Broadbent, Jonathan; Ram, Anumala (Frontiers in Oral Health, 2025)
IntroductionA growing body of literature reports on the oral health of Pacific peoples but a synthesis of the existing knowledge on Pacific oral health epidemiology is absent. This scoping review aims to summarise the evidence on Pacific oral health epidemiology. The findings of this review may help identify knowledge gaps and issues requiring health policy prioritisation.MethodsThe review followed the PRISMA-ScR guidelines for scoping reviews and included reports published prior to July 2023 on Pacific oral health, regardless of design. Searches were conducted across four databases, and the grey literature.ResultsAn analysis of 95 sources, primarily from 2000 to 2023 and predominantly New Zealand-based, found that a high proportion of Pacific peoples (including children) were affected by poor oral health and challenges in accessing dental care services. Numerous studies have reported oral health disparities, with poorer oral health among Pacific peoples than other population groups. Epidemiological and health services data from Pacific Island nations show a high prevalence of dental conditions, along with limited healthcare resources and workforce shortages. Studies on the broader social determinants shaping these issues and health promotion strategies to address them were limited.ConclusionThis review revealed significant unmet oral health needs, ethnic disparities in oral health, and barriers preventing care in Pacific populations. The findings emphasise the need for more research to address these gaps to help develop effective, culturally-informed oral health strategies for Pacific communities.